Decarbonization types of medium-sized and mid-cap firms in the manufacturing sector - Joern Block; Solvej Lorenzen; Holger Steinmetz (Business Strategy and the Environment, 2024)
The decarbonization of the manufacturing sector is needed to meet the climate goals set by the Paris agreement. Most research so far has focused on large firms. Yet, medium-sized and mid-cap firms also face increasing pressures to decarbonize, particularly in their role as suppliers of large firms. Prior research shows that these firms are very heterogeneous and that approaches to decarbonize are not adopted in isolation but within sets or configurations—hence, a detailed investigation of these configurations is fruitful to understand the multiplicity of responses to decarbonization. Such an understanding allows to develop an effective decarbonization policy for medium-sized and mid-cap firms and provide meaningful managerial advice. Using a latent-profile analysis, our study identifies five distinct decarbonization types of medium-sized firms in the German manufacturing sector that adopt a specific configuration of decarbonization strategies. These types can be described as decarbonization all-rounders , internal supply chain decarbonizers , total supply chain decarbonizers , decarbonization laggards and decarbonization sceptics . A comparison of these five decarbonization types reveals significant differences in stakeholder pressures, green capabilities and green innovation as well as firm performance and (structural) firm characteristics.
Keywords: 330; decarbonization; environmental sustainability; latent-profile analysis; manufacturing firms; medium-sized and mid-cap firms